Risky sexual practices and approaches to preventing sexually transmitted infections among urban dwelling older Yoruba men in Southwest Nigeria - Ojo Melvin Agunbiade; Leah Gilbert (Elsevier, 2023)
Social and cultural norms and beliefs shape how men, as social actors, perceive and engage in sexual activities. Little is known about risky sexual practices and prevention strategies among older Yoruba men. As a growing concern in Nigeria, this paper explores risky sexual behaviours of older Yoruba men living in Ibadan, a metropolitan city, and their strategies for preventing sexually transmitted infections in old age. We held six focus groups and nine semi-structured interviews, with a total of 65 participants. The findings show that social norms allow older men to engage in multiple sexual relationships, which exposes them to sexually transmitted infections (STIs), and to use potent traditional medical protective and preventive measures to mitigate their vulnerability to sexually transmitted infections and the consequences of having sex with women under "magun." Such measures include "magun" on men, incisions, amulets, and aseje (a traditionally prepared concoction). Additionally, the findings revealed that protective measures are against serious consequences of risky sexual behaviors, like sexual pleasures and death. The findings point to the need for more inclusive sexual health and HIV campaigns and strategies addressing the sexual health challenges of all men and women and must be culturally sensitive.